Representasi Penggunaan Bahasa Bugis terhadap Penggunaan Bahasa Indonesia Siswa Sekolah Dasar di Desa Balang Pesoang Kecamatan Bulukumpa Kabupaten Bulukumba - Ika Zulfika; B Syukroni Baso (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to answer the problem (question), whether there is Bugis language interference in the fields of morphology and syntax in writing Indonesian essays for elementary school students in Balang Pesoang Village, Bulukumpa District, Bulukumba Regency. The population in this study were all fifth grade students at SD Negeri No. 62 Waepejje, Balang Pesoang Village, Bulukumpa District, Bulukumba Regency, totaling 25 people with details of 10 men and 15 women, and the sample was determined within these students or in total. The instrument of this research is an Indonesian language exposition essay whose theme has been determined by the researcher. The data collection method used is a method that is analyzed in descriptive form. The results of the research show that there is a representation of the Bugis language in the use of Indonesian by class V students at SD Negeri No. 62 Waepejje Balang Pesoang Village, Bulukumpa District, Bulukumba Regency. Of the 25 samples who used Indonesian in writing essays, there were 13 forms of interference at the morphological level, and 12 forms of interference at the syntactic level. The results of further research show that in general the factors that influence the occurrence of Bugis language interference are because students are more familiar with Bugis language compared to Indonesian, the community environment is less supportive, and psychological factors that are always experienced by students, such as feelings that are always emphasized. From the results of this research, it can be concluded that the interference of the Bugis language in the use of Indonesian by class V students at SD Negeri No. 62 Waepejje, Balang Pesoang Village, Bulukumpa District, Bulukumba Regency, the causal factor being the strong influence of the Bugis language on students and as the family language that is most mastered and liked by its users by students.